It's politics, stupid! A political analysis of the HIV/AIDS Trust Fund in Uganda. Issue 4 (6th December 2019) - Birungi, Charles; Colbourn, Timothy
Abstract : The role of trust funds in the practice of and the policy discourse on the sustainable financing for health and HIV is growing. However, there is a paucity of political analyses on implementing trust fund arrangements. Drawing on a novel meta-framework – connecting multiple streams and advocacy coalition frameworks to policy cycle models of analysis – to politically analyse HIV financing policy design, adoption and implementation as well as insights from public finance literature, this article critically analyses the politics of the AIDS Trust Fund (ATF) in Uganda. We find that politics was the most fundamental driver for the establishment of the ATF. Whereas HIV financing is inherently both technical and political, enacting the ATF was largely a geopolitical positioning policy instrument that entailed navigating political economy challenges in managing multiple stakeholder groups' politics. With the mandated tax revenues earmarked to capitalise the ATF covering only 0.5% of the annual resource needs, we find a very insignificant potential to contribute to financial sustainability of the national HIV response per se. As good ideas and evidence alone often do not necessarily produce desired results, we conclude that systematic and continuous political analysis can bring meaningful insights to our understanding of political economy dimensions of the ATF as an innovative financing policy instrument, thereby helping drive technically sound health financing policy proposals into practice more effectively. For Uganda, while proponents have invested a considerable amount of hope in the ATF as a source of sustainable domestic funding for the HIV response, substantial work remains to be done to address a number of questions that continue to beguile the current ATF architecture. Regarding global health financing policy, the findings suggest the need to pay attention to the position, power and interests of stakeholders as a powerful lever in health financing policy reforms.